Can Criminal Procedure Ever Be “Modern”? A Historical Comparative Perspective (Editorial of the Dossier “History of Criminal Procedure in Modernity”) - Georges Martyn; Ricardo Sontag (Revista Brasileira de Direito Processual Penal, 2021)
This article is not a mere introduction to the dossier of the Revista Brasileira de Direito Processual Penal on “History of Criminal Procedure in Modernity” (composed of 13 contributions on Belgium, Brazil, Finland, France, Italy and The Netherlands), but it also touches upon three methodological questions of comparative legal history. The first one relates to the proper concept of “modernity”, which can be understood differently, not only in various scientific areas (sociology, history, legal history…), but also in different parts of the world (the French and English perceptions of the word designating different periods). The second one is the use of “models”, such as inquisitorial versus accusatorial procedures, or popular and lay courts versus professional justice administration. Can such kinds of concepts historically be attached to certain times and places, or should legal scholarship avoid to do so, acknowledging that all systems are always mixed? The third one claims that all comparative legal history ought to be contextual. The dogmatic (or ideal) developments of law, very often explained by referring to legal transplants and translations or hybridisations, can only really be understood by searching for factual factors, responsible for the impact of certain “foreign” ideas.